Management of diabetic retinopathy - Bacherini, Daniela (Developments in ophthalmology / series editor F. Bandello, 2017)
Recently developed diagnostic and therapeutic technologies such as OCT-angiography and small gauge vitrectomy have influenced the modern treatment of diabetic retinopathy. This volume provides a summary of the state-of-the-art evidence-based approach to managing complications that may occur with diabetic retinopathy. It offers the latest information on pathogenesis and diagnosis, and highly experienced clinicians review the results of relevant randomized clinical trials that serve as the basis of current therapy. The book provides not only a summary of data from randomized trials but also an analysis and interpretation by internationally renowned experts. Ophthalmology residents, fellows, and practicing clinicians will find this book to be a useful reference when seeking evidence-based treatment strategies for various complications of diabetic retinopathy. It is also for researchers identifying new avenues of drug developments and for insurance professionals and health care policy administrators who are establishing evidence-based therapy guidelines for therapeutic intervention.